STUDI PERBANDINGAN PEMETAAN RISIKO BENCANA LONGSOR BERBASIS PENDEKATAN NORMATIF DAN PENDEKATAN KUANTITATIF DI KABUPATEN GARUT - Hikmah, Nurul (Jurnal Pendidikan Geografi Gea, 2016)
Garut District is often affected by landslides. Based on data from researchs some landslides were induced by rainfall, slopes, type of soil, landuse, and geology. Some methods for a landslide risk zonation maps were created based on score and weight. So far only landslide hazard zonation maps created in Garut RTRW and PVMBG. Some of the results do not reflect actual data, as many landslides occur in  low hazard class. Therefore, it is needed to find  what appropriate method  to create land slide hazard and furthermore to risk map. This research aims to (1) Evaluate normative based hazard mapping (score and weight approach) and quantitative (real data in research area) based in Garut, (2) Evaluate mapping based vulnerability-based land use, (3) Evaluate  risk level in Garut. The results showed that the formula for assessing hazard based on scores and weighting parameters following government method of BNPB (2012)as Landslide Hazard = 0,25*Land Use and Conservation + 0,35*Soil + 0,40*Slope,  and based on scores and weighting parameters from actual  landslide extracted from Linear Regression Analysis as Landslide Hazard = - 2, 059 + 1,762* Land Use and Conservation + 0,022*Soil + 0,002*Slope. The formula for assessing vulnerability is V = ((0,5* Land Use and Conservation) + (0,2*Population Density) + (0,3*Land Rent)). The formula of landslide risk is R = H x V. Based on these formulas, landslide hazard map quantitative method has a correlation value of R2 = 0.907. The high vulnerability class chraracterised by conservation of contour strip cropping to crop carrots and the cabbage have the highest vulnerability classes.  Distribution of the high hazard class almost uniformly in the research area. The high landslide risk class has an area of 17.25 hectares, or 30.62 % of research area. Keywords: landslide, risk mitigation, normative and quantitative approaches, Garut.